FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS (Studi Pada Perusahaan Manufaktur di BEI) - Fatmawati, Amelia; Wahidahwati, Wahidahwati (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchis aimed to find out the influence of good corporate governance, operating efficiency, profit benefits and cash flow from operating activities to the financial distress through annual financial reports which have been prepared by manufacturing companies which arelisted in Indonesia Stock Exchange.The population in this research has been obtained by using purposive sampling method to the manufacturing companies which arelisted in Indonesia Stock Exchange (IDX) with predetermined criteria i.e. manufacturing companies which have financial statements data in 2011-2015 periods, manufacturing companies which have experienced interest coverage ratio less than one, and manufacturing companies which use rupiah as their reporting currency. Based on the research method, 190 manufacturing companieshave beenselectedas samples. The analysis method has been performed by using logistic regression analysis and the SPSS application tools (Statistical Product and Service Solutions).The results of this research indicate that the variables of operating efficiency, profit benefits and cash flow from operating activities give positive influenceto the financial distress. Meanwhile, good corporate governance givesnoinfluenceto the financial distress.Keywords: good corporate governance, operating efficiency, profit benefit, cash flow from operatingactivities, financial distress.